The Subjugated Woman ‘SELF’ in Kalidas’s ‘Shakuntala’ - Aryal, Kamana (Butwal Campus Journal, 2024)
This research paper tries to inculcate the epiphany Shakuntala experiences once she is insultingly evicted from the palace of the king, Dusyanta. Although she devoted herself to Dusyanta blindly, he denounces to accept Shakuntala his wife. A disparaged betrayed pregnant wife leaves the palace and births the child in the midst of forest. Her real struggle in quest of her ‘self’ and nurturing her son singly is the most captivating scenario of this epic. The king’s abandoning Shakuntala corroborates novice strength in her which leads to her further recognition about her position as a beloved and a wife. The broader umbrella term called “Feminism” somehow nearly ignores the south Asian and Third World feminine traumas. Thus, this research paper uses several transnational feminist theories to justify Shakuntala’s journey of self evolution.